DISTRIBUSI KAMBING HUTAN SUMATERA[CAPRICORNRS SUMATRAENSIS SUMATRAENSIS (BECHSTEIN, 1799)] DI SIPURAK, TAMAN NASIONAL KERINCI SEBLAT, SUMATERA - Susanti, Neneng; Mardiastuti, Ani; Andayani, Noviar (JURNAL BIOLOGI INDONESIA, 2006)
ABSTRACTSumatran Serow Capricornis sumatraensis sumatraensis (Bechstein, 1799))Distribution at Sipurak-Kerinci Seblat National Park. Sumatran serow [Capricornissumatraensis sumatraensis (Bechstein, 1799)J is one of endangered species in KerinciSeblat National Park (KSNP). Few data are available about Sumatran serow in KSNP.The research was designed to analize the distribution of Sumatran serow in Sipurak.Fieldstudy was conducted from September 2005 to February 2006 in Sipurak, KSNP.The detection-non detection survey method was applied for observation. There were 44cells sampling,' the number of cells determined by purposive sampling base on habitattypes and accessibility to reach the location of cell (easy or hard). The data were analyzedby Arcview 3.2 PC. The sumatran serow just indirectly detected. Sign of its existencemainly detected at ramp. Distribution of sumatran serow mainly was invented on the lowland forest type (8 1,82%) which are characterized by caves, rock-cliff, and rugged hills.Key words: Distribution; detection-non detection; sumatran serow; Sipurak